2011
DOI: 10.3109/00016489.2011.635385
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the cupula after disruption of the membranous labyrinth

Abstract: Various kinds of cupular changes including shrinkage were observed. Cupular change was more severe after a longer survival period. Large or elongated volume of the cupula was also observed, which was not observed in our previous study using gentamicin. The CAP could be recorded even when the cupular change was severe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It is expected that the movement of the cupula will change as it shrinks. Kondo et al observed similar cupular changes after puncturing the membranous labyrinth 17 . The cupula was also found to change in a high osmolarity environment 18 .…”
Section: Discussionmentioning
confidence: 82%
“…It is expected that the movement of the cupula will change as it shrinks. Kondo et al observed similar cupular changes after puncturing the membranous labyrinth 17 . The cupula was also found to change in a high osmolarity environment 18 .…”
Section: Discussionmentioning
confidence: 82%
“…To the best of our knowledge, morphological changes in the cupula have never been reported in studies on the human temporal bone. According to animal models, the cupula shrinks into the inner ear after gentamicin injection and enlarges after disruption of the membranous labyrinth [ 13 , 14 ]. When the cupula becomes enlarged and the mass remains constant, its relative density should decrease.…”
Section: Discussionmentioning
confidence: 99%
“…potential. Even when the cupula is severely damaged the physiological activity of the sensory epithelia is maintained 114,115 . They assume that when the cupula shrinks, the activity to stimuli is reduced and thereby caloric response.…”
Section: Lateralization Of Affected Side By Ewald's Second Lawmentioning
confidence: 99%